2020
DOI: 10.1109/tit.2019.2941744
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Constructions of MSR Codes for Clustered Distributed Storage: The Rack-Aware Storage Model

Abstract: The paper is devoted to the problem of erasure coding in distributed storage. We consider a model of storage that assumes that nodes are organized into equally sized groups, called racks, that within each group the nodes can communicate freely without taxing the system bandwidth, and that the only information transmission that counts is the one between the racks. This assumption implies that the nodes within each of the racks can collaborate before providing information to the failed node. The main emphasis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 38 publications
0
72
0
Order By: Relevance
“…In this section, we consider the repair scheme for multiple failed nodes for a known construction in [4] by Chen and Barg. Although there is a known optimal repair scheme for a single failed node, the repair scheme for multiple failed nodes is still open.…”
Section: A Class Of Mscr Codesmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we consider the repair scheme for multiple failed nodes for a known construction in [4] by Chen and Barg. Although there is a known optimal repair scheme for a single failed node, the repair scheme for multiple failed nodes is still open.…”
Section: A Class Of Mscr Codesmentioning
confidence: 99%
“…First of all, we recall the known construction of MSR codes in [4]. Let n, k, d, r, s, and N be positive integers, where…”
Section: A a Construction Of Mcsr Codesmentioning
confidence: 99%
See 2 more Smart Citations
“…More surprisingly, in recent years a new interest in these codes has risen in the research community. It is caused by the fact that they are extensively used in cloud technology, namely in distributed storage systems [5,6,7,8,9]. In [1] it was shown that RS codes could be extended not only three times, but even five times when they are constructed over certain finite fields.…”
Section: Introductionmentioning
confidence: 99%